Difficult Intubation Are You Prepared for It - Balcom, Corina (Operating Room Nurses Association of Canada Journal, 1994)
The endotracheal intubation of a patient for surgery requires an anaesthetist who is aided by a skilled and experienced helper. This paper explores reasons why some patients are difficult to intubate. Some are predictable on pre-operative assessment and others are not. Suggestions are given on how the helper is useful to the anaesthetist in this potentially critical situation.